Analysis of Requirements for the Creation of Edukiwari Learning Media Applications for Curriculum Designing Materials in Culinary Tourism Vocational High Schools - Gunawan, Aditia Gustiana; Mariana, Rina Rifqie Mariana; Umam, Nada Itorul; Joshua, Quienera (Journal of Vocational Education Studies, 2025)
The appearance of digital technology has transformed society into a life-oriented learning community, and learning activities, which originally took place offline, need to be transferred online. The integration of ICT in education by using the TPACK framework is no longer an option but an obligation. In Cookery subjects at tourism vocational schools, current learning media mostly consist of PowerPoint and printed books. This paper is intended to develop an Android-based application of Food Service Learning Media that could provide the possibility for the teaching and learning process and enhance critical thinking. Information from 3 participants to find out what students and teachers need through the FGD method shows that integration of knowledge of content, pedagogy, and technology is needed in the mobile menu book. It would also include in the application some very interactive elements which help enhance student learning and are missing from current culinary education, therefore making current culinary education more effective.